The Fiscal Dimensions of Adjustment in Low-Income Countries - Gupta, Sanjeev; Liuksila, Claire; Lorie, Henri; Mahler, Walter (Washington, D.C. : International Monetary Fund, 1992)
A strengthened fiscal position is at the core of most economic adjustment programs supported by IMF lending, especially for the poorer countries that draw on the IMF's structural adjustment facilities. This paper reviews developments in 23 countries and evaluates their experience with fiscal and structural adjustment, including their efforts to design social safety nets to cushion the effects of adjustment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet